Markers for mapping trypanotolerance genes - Kemp, Stephen J.; Teale, A.J. (International Laboratory for Research on Animal Diseases, 1994)
Several West African Bos taurus cattle breeds show a remarkable ability to survive and be productive in the face of a trypanosome challenge which would quickly kill susceptible cattle. This phenomenon, termed trypanotolerance, offers a sustainable approach to improving cattle productivity in the tsetse-infested areas of Africa. The best charaterized of the trypanotolerant breeds is the N'Dama. A genome analysis approach is adopted in an attempt to identify analysis approach is adopted in an attempt to identify the genetic basis for trypanotolerance in the N'Dama. A cross between N'Dama and trypanosusceptible Boran (B. indicus) has been established using embryo-transfer to generate large full-sibling families. The F1 generation is almost complete and 14F2 calves were boran by April 1993. These will be challenged with several other laboratories, they will be genotyped with a large array of genetic markers. Correlations will then be sought between marker inheritance and trypanotolerance status. These markers fall into three main categories. 1. Randomly amplified DNA polymorphisms. 2. Randomly identified polymorphic dinucleotide repeat sequence (microsatellites). 3. Polymorphisms in specific genes.